Dormancy in yams - Craufurd, Peter Q.; Summerfield, R.J.; Asiedu, Robert; Prasad, P. (Cambridge University Press, 2001)
The tubers of yam, principally those of Dioscorea rotundata (white Guinea yam) and D. alata (water or greater yam), are important staple foods and sources of carbohydrate in West Africa. Yams are grown in diverse environments – from the high-rainfall forest zone on the coast to the seasonally arid savannas of West Africa, that is in situations in which the duration and the timing of the onset of the growing season vary appreciably. Dormancy in both underground and aerial tubers of the Dioscoreaceae is an important adaptive mechanism that helps to maintain organoleptic quality during storage and also ensures that tubers germinate at the start of the growing season. Plant breeders are especially keen to manipulate the duration of the dormant period in order to synchronize growth periods and, therefore, to produce more than one generation per year. The control of tuber dormancy, however, is poorly understood. This review examines critically those factors that affect tuber initiation, dormancy and sprouting, and makes recommendations for future priorities in research.